2015
DOI: 10.15448/2357-9641.2014.1.20081
|View full text |Cite
|
Sign up to set email alerts
|

Um estudo transversal sobre atividade física e qualidade de vida relacionada à saúde em idosos institucionalizados e não institucionalizados

Abstract: A cross-sectional study on physical and sedentary activity and health-related quality of life in institutionalized vs. non-institutionalized elderly Differences between institutionalized and non-institutionalized elderly were found in moderate-intensity activities and walking, a favour of non-institutionalized. The institutionalized elderly remain more minutes in sedentary activity. Also, were observed differences between both groups in physical component of HRQoL, a favour of non-institutionalized elderly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Although there are significant differences between groups in moderate PA, in both cases the results revealed patterns of PA very distant from the health recommendations of accumulating at least 30 min of moderate to vigorous PA (World Health Assembly 2004) or 10,000 steps per day (Tudor-Locke & Bassett, 2004). There are a limited number of studies that measured PA in institutionalized older adults or DCC users and most of them have reported PA by questionnaire (Król-Zielinska et al, 2011;Pereira et al, 2016;Tomas-carus et al, 2014). A previous study about PA behavior which was also conducted with Portuguese institutionalized older adults (Lobo, Santos, Carvalho, & Mota, 2008), reported better results than ours.…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…Although there are significant differences between groups in moderate PA, in both cases the results revealed patterns of PA very distant from the health recommendations of accumulating at least 30 min of moderate to vigorous PA (World Health Assembly 2004) or 10,000 steps per day (Tudor-Locke & Bassett, 2004). There are a limited number of studies that measured PA in institutionalized older adults or DCC users and most of them have reported PA by questionnaire (Król-Zielinska et al, 2011;Pereira et al, 2016;Tomas-carus et al, 2014). A previous study about PA behavior which was also conducted with Portuguese institutionalized older adults (Lobo, Santos, Carvalho, & Mota, 2008), reported better results than ours.…”
Section: Resultscontrasting
confidence: 58%
“…A previous study about PA behavior which was also conducted with Portuguese institutionalized older adults (Lobo, Santos, Carvalho, & Mota, 2008), reported better results than ours. The authors divided the sample into tertiles according to min of moderate PA, reporting mean values between 0.6-0.7 min, 4.3-4.7 min and 25.6-27.9 min for each of those tertiles, thus showing that about one-third of the participants have reasonable levels of PA. We have also found two studies (Pereira et al, 2016;Tomas-carus et al, 2014) that reported results for PA behavior as measured by the International Questionnaire of Physical Activity (Craig et al, 2003). Tomas-carus et al (2014) showed good results of PA in institutionalized older adults.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation